Piezoelectric polymer membranes with thin antibacterial coating for the regeneration of oral mucosa; Applied Surface Science; Vol. 504 - Badaraev A. D. Arsalan Dorzhievich; Koniaeva A. Aleksandra; Krikova S. A. Svetlana Aleksandrovna; Shesterikov E. V. Evgeny Viktorovich; Bolbasov E. N. Evgeny Nikolaevich; Nemoykina A. L. Anna Leonidovna; Buznik V. M. Vyacheslav Mikhaylovich; Stankevich K. S. Ksenia Sergeevna; Zhukov Yu. M. Yuriy Mikhaylovich; Mishin I. P. Ivan Petrovich; Varakuta E. Yu. Elena Yurjevna; Tverdokhlebov S. I. Sergei Ivanovich (2019, 2019)
Title screen